The Application of a Three-factor Model for Investing on the Warsaw Stock Exchange - Schmidt, Bartłomiej (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Since the 1970s numerous papers have presented the results of analyses conducted on western capital markets. They have provided a great deal of evidence that CAPM is not able to deliver valuable predictions about future stock returns. That is why so many attempts have been made to develop a better pricing model, one of which is Fama and French’s three-factor model. This article analyses the extent to which this model can predict stock returns on the Warsaw Stock Exchange (the WSE). The analysis shows that the three-factor model does not deliver accurate predictions because it does not take into account all the essential factors that determine returns on the WSE. Further surveys should be conducted to identify these factors.